Examining Mothers’ Exposure to Community Violence: How Does it Influence Young Adolescents? - Jocson, Rosanne M (Archīum Ateneo, 2021)
Background An expansive literature on community violence exposure has almost exclusively focused on its effects on children, yet little is known about the effects of exposure to community violence on parents. Similarly, a wealth of research has investigated the impact of intimate partner violence, but not community violence, on mothers. Objective This longitudinal study investigates how mothers’ exposure to community violence is associated with maternal well-being and young adolescents’ internalizing and externalizing behaviors, after controlling for maternal exposure to intimate partner violence and children’s exposure to violence. Methods With a multiethnic sample of 779 mothers and children, we conducted structural equation modeling using secondary data from the Project on Human Development in Chicago Neighborhoods. Results Findings revealed that, after controlling for maternal exposure to intimate partner violence and child victimization and witnessing violence, mothers’ exposure to community violence was concurrently linked to higher levels of maternal depressive symptoms. In turn, maternal depressive symptoms were longitudinally associated with higher levels of internalizing and externalizing behaviors during preadolescence. Results also indicated a statistically significant indirect relation between mothers’ witnessing of community violence and young adolescents’ internalizing and externalizing behaviors through maternal depressive symptoms. Conclusions Our findings underscore the need to adopt a broader family systems approach in examining the effects of community violence exposure and highlight the potential benefits of reducing both children’s and mothers’ exposure to community violence to improve mothers’ psychological well-being and adolescent outcomes.